VD_FINDINFO Jug / 2010 / 28 vom 16. März 2010 - VD Tribunal cantonal (2010)
ASSURANCE COMPLÉMENTAIRE, VIOLATION DE L'OBLIGATION D'ANNONCER, CONTRAT D'ASSURANCE | 1 DTAs-AM, 4 LCA, 6 LCA, 9 LCA, 106 LPA-VD, 109 LPA-VD, 55 LPA-VD